36mn-4m=

Simple and best practice solution for 36mn-4m= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36mn-4m= equation:


Simplifying
36mn + -4m = 0

Reorder the terms:
-4m + 36mn = 0

Solving
-4m + 36mn = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '4m'.
4m(-1 + 9n) = 0

Ignore the factor 4.

Subproblem 1

Set the factor 'm' equal to zero and attempt to solve: Simplifying m = 0 Solving m = 0 Move all terms containing m to the left, all other terms to the right. Simplifying m = 0

Subproblem 2

Set the factor '(-1 + 9n)' equal to zero and attempt to solve: Simplifying -1 + 9n = 0 Solving -1 + 9n = 0 Move all terms containing m to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 9n = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 9n = 0 + 1 9n = 0 + 1 Combine like terms: 0 + 1 = 1 9n = 1 Add '-9n' to each side of the equation. 9n + -9n = 1 + -9n Combine like terms: 9n + -9n = 0 0 = 1 + -9n Simplifying 0 = 1 + -9n The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

m = {0}

See similar equations:

| 16h=19 | | n-3.2=56 | | -63-(-4)= | | 2(w+3)-7w=11 | | lnx=x^3+8 | | (y^2+2xy)-(x^2)dx=0 | | 0.11y=-9 | | 1.5m=11 | | 1.3=8.02 | | 4x+2-3x=10 | | -27=3(x-5)-5x | | -6+13x+-1x^2+-2x^3=0 | | y=-10-1 | | 75=d+15 | | 3x^2-4x+1024=0 | | -15n-20=12n-20 | | 4(8x-7)-7(6-7x)= | | 13x+30=3x+160 | | 72/(-9) | | 4z=-56 | | 8(10x+2)-(7+5x)= | | y=2x^3+12x^2-6x | | 6=13r | | 70=G-50 | | 5(v+5)-7v=15 | | -7+9=m-7 | | y+2(6)=0 | | 132-6x=4x+2x^2 | | -6u+2(u-5)=6 | | y+2(-4)=0 | | X^2-x+15=113 | | 30=5(y+4)-7y |

Equations solver categories